The Relationship of Modified Bismuth and Ninhydrin Methods with Periodontal Pathogens in Saliva - Piamsiri, Cholthicha; Youravong, Nattaporn; Teanpaisan, Rawee; Thananimit, Suchera; Hunsrisakhun, Jaranya (Trends in Sciences, 2025)
Periodontal diseases are prevalent and chronic oral conditions. This study was conducted to determine the performance, validity, and applicability of the modified bismuth and ninhydrin methods to detect bacterial degradation for the development of periodontal screening tools. The experiments were conducted to test the performance and validity of both methods using standard solutions and evaluate their applicability using human saliva. Spearman’s correlation was used to find the correlation between the quantity of periodontal pathogens, salivary H2S, and total amines. The experiments showed good performance. The bismuth solution had a limit of detection (LOD) of 1-2 ppm NaHS. The stability test revealed that the 23-week bismuth solution produced the same quantity of bismuth sulfide precipitate as fresh preparations under optimal conditions. The validity test showed acceptable results. The color intensities of the modified ninhydrin method were quantified. The intensity of ∆G was chosen for the quantitative detection of total amines due to its strong correlation with putrescine concentration. The calibration curve exhibited linearity over putrescine concentrations ranging from 0.5 to 4.0 mM (R2 = 0.929). The precision test showed that %RSD ranged from 2.40 to 22.50. The applicability tests demonstrated that both methods detected and scored salivary H2S and total amines in relation to the quantity of analytes. Three periodontal pathogens—F. nucleatum, P. gingivalis, and P. intermedia—were significantly correlated to salivary H2S. Only F. nucleatum was significantly correlated to salivary total amines. The results of this study indicate that the modified bismuth and ninhydrin methods can effectively identify periodontal degradation with acceptable performance and validity. HIGHLIGHTS Periodontal diseases are prevalent and chronic conditions that inflict damage on both the hard and soft tissues of the periodontium. Conducting a thorough periodontal examination on a large population requires the expertise of highly qualified practitioners and the use of precise diagnostic tools. In this study, we estimated the levels of salivary hydrogen sulfide (H₂S) and total amines using the modified bismuth and ninhydrin methods. The findings suggest that these modified methods provide satisfactory performance and validity and can effectively identify periodontal metabolites. GRAPHICAL ABSTRACT